Modified Rejection Ratio for Multiple Load Cases Evolutionary Structural Optimization - Hu, Xing-guo; Cheng, He-ming; Tao, Yan (Procedia engineering, 2012)
At present, for topological optimization in multiple load cases, many researchers use directly traditional Evolutionary Structural Optimization (ESO) method to get respectively the inefficient material set that should be removed in each load case, then the intersection of all the sets is just the material that should be removed. This Multiple Load Cases Traditional ESO (MLCTESO) is difficult to optimize a structure subject to complex load cases, and the optimization result may not be reasonable. Modified Rejection Ratio for Multiple Load Cases Evolutionary Structural Optimization (MRR-MLCESO) proposed in this paper makes a change based on the MLCTESO. The major change is to modify the rejection ratio of each load case according to the ratio of the total strain energy of a structure subject to each load case to the total strain energy of a structure subject to all load cases, then optimization for a structure subject to complex multiple load cases can be easily made and the structure obtained from such an optimization has a good undertaking force performance.